Competitive strategy assessment of Malaysian wooden furniture manufacturer. - Ziaie, Mohsen (2011)
Despite the strong growth of the Malaysian furniture industry over the last two decades, evidences suggest that the industry's growth in the global market is declining. A drop in the annual export rate, global market share, and unit product price are testimonies implying that the industry is currently facing escalating competition in the export markets. Hence, the main goal of the study was to analyze the industry's competitive environment to find the key forces driving the industry's profitability in association with the competitive strategies and strategic trends in the industry. Porter's theory, comprising the five-force model and generic competitive strategies, was employed to achieve the research objective. This study identified the competitive forces driving the competitive environment in the Malaysian wooden furniture industry in the exports markets. We evaluated 23 strategic activities and the overall competitive strategies of the sampled companies in the industry at the time of the study (June to November 2009) and for the near future (next five years). Furthermore, the effects of the firm's size and market on the formation of the competitive forces and strategies were examined. Strategic groups among the companies were tracked and finally the effects of the competitive forces on the firm's performance in association with the corresponding competitive strategy were evaluated. The results of this research were drawn from data manipulation and statistical analysis and testing, using several multivariate statistical techniques. The results showed that "the intensity of rivalry" within the industry, coupled with "the bargaining power of buyers" are the two key factors driving the competitive environment and determine profitability of the industry. In addition, these two factors have the most pronounced effects on the firm's performance as a function of the practice, extent, and level of implementation of competitive strategy. Meanwhile, "the bargaining power of suppliers" was identified as a potential competitive force which will pose severe pressure on the competitive environment of this industry. An evaluation of strategic activities and three overall competitive strategies at the time of the study and for the near future demonstrated that this industry does not currently follow a distinct competitive strategy. This could be considered as an explanation of the origin of the current decline in the industry’s growth rate in the global markets. However, for future growth and prosperity, the industry is developing its strategic activities in distinctive strategic orientations, specifically Differentiation, Cost leadership, and Focus. Investigation of the companies'strategic activities enabled us to identify four strategic groups illustrating the current and future strategic trends in the industry. Furthermore, the research findings indicated that the firm's size and the market have effects on the formation of the competitive forces and strategies. The findings of this research demonstrated that the industry faces intensive competition which has arisen from its stuck in the OEM strategy with resource based view, and negligence to competitive strategy view. Hence, the industry's future growth and success depends entirely on developing appropriate competitive strategies by the companies.